Comparative evaluation of Allplex HPV28 and Anyplex II HPV28 assays for high-risk HPV genotyping in cervical samples - Sarah Mafi; Flavie Theuillon; Sylvain Meyer; Jean-Baptiste Woillard; Marine Dupont; Sylvie Rogez; Sophie Alain; Sébastien Hantz (PLoS ONE, 2025)
Background/Objectives Human papillomavirus (HPV) genotyping is essential for cervical cancer screening and prevention. The AllplexTM HPV28 real-time PCR kit, using different chemistry and results analysis compared with its predecessor, the AnyplexTM II HPV28 kit, has recently been launched. This study aims to compare the AllplexTM HPV28 and AnyplexTM II HPV28 assays in detecting and genotyping the 13 high-risk (HR)-HPV types. Study design Between 2022 and 2023, 459 cervical samples from women undergoing cervical cancer screening were selected. These samples were analysed by liquid-based cytology and tested by both kits concurrently. Results AllplexTM HPV28 Ct values correlated well with AnyplexTM II HPV28 signal intensity scores. No significant differences between assays were observed in overall and genotype-specific HR-HPV prevalence determined in all samples and according to cytological results. In addition, no significant differences were identified between assays in the detection of single and multiple HR-HPV infections. Most of the discordant results corresponded to samples showing weak HR-HPV signals and multiple HR-HPV types. Conclusions Our results demonstrate that the AllplexTM HPV28 kit can be used for HPV genotyping, with results overall similar to those obtained with the AnyplexTM II HPV28 kit and the addition of Ct values for patient follow-up. The clinical implications of the potentially reduced sensitivity of the AllplexTM HPV28 kit in detecting HPV31 (p =  0.07) and HPV39 (p =  0.08) warrant further investigation in subsequent studies.